Analisis Konsumsi Energi Listrik Pompa Sirkulasi Cooling Tower P21C Menggunakan Inverter di PT Unilever Oleochemical Indonesia - Yoel Wesly Dirney Lumbantoruan; Parlin Siagian; Haris Gunawan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The cooling tower circulating pump circulates cooling water throughout the cooling system by controlling the rotation of the circulating pump using an inverter. The method in this research uses quantitative methods. The research aims to analyze two circulating pump units with and without inverter. The results of one year of research on circulation pumps without inverter consumed 48,180 kWh of electrical energy and circulation pumps with inverter consumed 31,083.4 kWh of electrical energy, the resulting electrical energy savings was 17,096.6 kWh at a cost of IDR 19,058,263.9. Using an inverter can save electric energy consumption because the speed of the circulation pump can be adjusted, which causes the output voltage to vary and not always remain constant at the maximum value, so the electric energy consumption is lower.